Analisis Bilangan Peroksida, Organoleptik, dan Proksimat Abon Tuna dengan Fortifikasi Jantung Pisang - Muhammad Dailami; Delvira Riska Ananta; Heder Djamaludin; Hardoko Hardoko; Vivi Nurhadianty; Dean Rama Prayoga (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
Fish is part of the diet which is a source of animal protein which is very beneficial for health. To meet the availability of fish-based food, it can be processed into various processed products, one of which is shredded fish. Shredded fish still has a drawback, such as the low fiber content. To enrich the fiber content of shredded fish, fortification with banana blossoms can be an alternative. The process of making shredded fish does not yet have a standard because many methods and spices are added, so there are variations in the types and amounts of spices used. This causes the quality of shredded fish to vary. Therefore, this study aimed to evaluate the chemical properties of the effect of different concentrations on banana blossoms fortification in the processing of shredded tuna. The research was conducted in June-August 2022 at the Fish Product Technology Laboratory and the Chemical Engineering Laboratory, Universitas Brawijaya. The study design was a non-factorial Completely Randomized Design (CRD). The results were analyzed using ANOVA (α 5%) and Tukey's post hoc test. The results showed that banana blossoms fortification had no significant effect on the peroxide value and water content of shredded tuna. Banana blossoms fortification has a significant effect on the hedonic value of the appearance, taste, and texture of shredded tuna. However, it has no significant effect on the hedonic aroma value and overall acceptance. The value of the proximate composition of shredded tuna with the best treatment level was 70%, i.e. protein content of 14.51%, fat content of 36.19%, ash content of 6.82%, carbohydrate content of 29.15%, and total dietary fiber of 20.80%. The fat and protein content of shredded tuna does not meet the Indonesian National Standard (SNI) for shredded products.